Oral hygiene and sugar consumption among urban and rural adolescents in Ghana - Blay D, Åstrøm AN, Haugejorden O (Blackwell Synergy, 2000)
The purpose of this study was to compare categories of self-reported oral health behavior among adolescents raised in urban and rural areas of Ghana. Methods: Second year students (n½583) aged 14–18 years were selected from the five secondary schools in the Awutu-Effutu Senya district, using a stratified random sampling procedure. A total of 504 (86%) students completed questionnaires under supervision at school.